Autonomous Sales Robot untuk Pengenal Produk Berbasis Barcode dan Arduino ATMega328 - Ikhsan Ikhsan; Ade Afdhika Putra (Ikatan Ahli Informatika Indonesia (IAII), 2018)
This paper discusses similar machines of people who are categorized as robots that function as product identifier sales. This research is used as a substitute for shop assistants who sometimes have an emotional attitude when the consumer asks many things. By utilizing this robot, is expected to provide more services to consumers, consumers only need to show the goods that will be desired to the robot by closing the barcode, and the robot will provide information to the product in detail. In the process of this research is made by waterfall method with the necessary changes. From the results of the study concluded that the robot system can provide information services to consumers